Let battle commence. (Economist, 2002)
Reports on competition between Microsoft Corp. and other software companies between Microsoft's .NET web services software platform and the popular Java 2 Platform Enterprise Edition (J2EE). Arguments for each product; How Java became a popular platform for Internet-based programs; Efforts of Microsoft to create a platform that offers development tools and Extensible Markup Language (XML).